FODMAPs alter symptoms and the metabolome of patients with IBS: a randomised controlled trial. Issue 7 (14th March 2016) - McIntosh, Keith; Reed, David E; Schneider, Theresa; Dang, Frances; Keshteli, Ammar H; De Palma, Giada; Madsen, Karen; Bercik, Premysl; Vanner, Stephen
Abstract : Objective: To gain mechanistic insights, we compared effects of low fermentable oligosaccharides, disaccharides and monosaccharides and polyols (FODMAP) and high FODMAP diets on symptoms, the metabolome and the microbiome of patients with IBS. Design: We performed a controlled, single blind study of patients with IBS (Rome III criteria) randomised to a low (n=20) or high (n=20) FODMAP diet for 3 weeks. Symptoms were assessed using the IBS symptom severity scoring (IBS-SSS). The metabolome was evaluated using the lactulose breath test (LBT) and metabolic profiling in urine using mass spectrometry. Stool microbiota composition was analysed by 16S rRNA gene profiling. Results: Thirty-seven patients (19 low FODMAP; 18 high FODMAP) completed the 3-week diet. The IBS-SSS was reduced in the low FODMAP diet group (p<0.001) but not the high FODMAP group. LBTs showed a minor decrease in H2 production in the low FODMAP compared with the high FODMAP group. Metabolic profiling of urine showed groups of patients with IBS differed significantly after the diet (p<0.01), with three metabolites (histamine, p-hydroxybenzoic acid, azelaic acid) being primarily responsible for discrimination between the two groups. Histamine, a measure of immune activation, was reduced eightfold in the low FODMAP group (p<0.05). Low FODMAP diet increased Actinobacteria richness and diversity, and high FODMAP diet decreased the relative abundance of bacteria involved in gas consumption. Conclusions: IBS symptoms are linked to FODMAP content and associated with alterations in the metabolome. In subsets of patients, FODMAPs modulate histamine levels and the microbiota, both of which could alter symptoms. Trial registration number: NCT01829932.